Job satisfaction of physiotherapists employed in the medical rehabilitation process - Sudar, Danijela; Trajkov, Marija T.; Kljajic, Dragana; Grbic, Gordana; Simpraga, Ljiljana (Education and Research in Health Sciences, 2023)
Introduction: Many professions in modern society are being greatly challenged, and the work productivity of employees is of great interest for conducting good business. Job satisfaction is certainly one of the factors that influence work productivity. As a multidimensional and complicated construct, job satisfaction includes internal  and external dimensions. Professional dissatisfaction is often cited by healthcare workers who are exposed toincreased risk primarily due to stress, burnout at work, maintaining a balance between one's private life and work, as well as due to the increasing burden of diseases and lack of manpower.Objective: To examine job satisfaction among physiotherapists, their stress levels, work productivity, and quality of life.Methodology: The research was done as a cross-sectional study. Using the Job Satisfaction Questionnaire, the Work Stress Questionnaire, the Working Ability Index, and the Quality of Life Questionnaire, we surveyed physiotherapists of both sexes, who are aged 20 and over and employed at the "Dr. Miroslav Zotović" Rehabilitation Clinic in Belgrade.Results: 87 respondents with an average age of 43.20 years participated in the research. The average work experience of the respondents is 18.68 years, while the respondents have spent an average of 12.61 years in their current workplace. The respondents expressed the greatest satisfaction with the attitude of the patients towards them, as well as with the direct cooperation with colleagues. The lowest satisfaction was related to the financial compensation for one's work. The results thus indicate that inadequate financial compensation, inadequate material resources for work, and an inadequate work space are the most common stressors.Conclusion: Physiotherapists are satisfied with their work. The greatest satisfaction is reflected through the attitude of patients towards physiotherapists, as well as through the cooperation with colleagues.
Keywords: job satisfaction; stress; health workers; physiotherapists